Two New 1,3,4-Oxadiazoles With Effective Antifungal Activity Against Candida albicans - Capoci, Isis Regina Grenier; Sakita, Karina Mayumi; Faria, Daniella Renata; Rodrigues-Vendramini, Franciele Abigail Vilugron; Arita, Glaucia Sayuri; de Oliveira, Admilton Gonçalves; Felipe, Maria Sueli; Maigret, Bernard; Bonfim-Mendonça, Patricia de Souza; Kioshima, Erika Seki; Svidzinski, Terezinha Inez Estivalet (Frontiers in Microbiology, 2019)
Candida infections have become a serious public health problem with high mortality rates, especially in immunocompromised patients, being Candida albicans the major opportunistic pathogen responsible for systemic or invasive candidiasis. Commercially available antifungal agents are restricted and fungal resistance to such drugs has increased; therefore, the development of a more specific antifungal is necessary. Using assays for antifungal activity, here we report that two new compounds of 1,3,4-oxadiazoles class (LMM5 and LMM11), which were discovered by in silico methodologies as possible thioredoxin reductase inhibitors, were effective against C. albicans. Both compounds had in vitro antifungal activity with MIC 32 μg/mL. Cytotoxicity in vitro demonstrated that LMM5 and LMM11 were non-toxic in the cell lines evaluated. The kinetic of time-kill curve suggested a fungistatic profile and showed a inhibitory effect of LMM5 and LMM11 in 12 hours that remained for 24 and 36 hour, being better than fluconazole. In the murine systemic candidiasis model by C. albicans, the two compounds reduced significantly the renal and spleen fungal burden. According to the SEM and TEM images, we hypothesized that the mechanism of action of LMM5 and LMM11 is directly related to the inhibition of the enzyme thioredoxin reductase and they affected internally fungal cell. In view of all in vitro and in vivo results, LMM5 and LMM11 are effective therapeutic candidates for the development of new antifungal drugs addressing the treatment of human infections caused by C. albicans.